2019
DOI: 10.3906/sag-1807-67
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between intestinal Behçet’s disease and Crohn’sdisease based on endoscopy

Abstract: Background/aim: Differentiating intestinal Behçet's disease (BD) from Crohn's disease (CD) is highly challenging, as they often mimic each other in terms of clinical manifestations. Endoscopy is an important modality for distinguishing bowel lesions. The study was designed to identify clinical manifestations that are easily confused and to evaluate the efficacy of endoscopy for distinguishing intestinal BD from CD by several overlapping signs. Materials and methods: The data from 111 patients with intestinal B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…Under colonoscopy, ≤5, round, focal, non-aphthous and non- cobblestone lesions were suggestive of intestinal BD, whereas longitudinal and multiple ulcers were suggestive of CD. The AUC of colonoscopy was 0.874-0.955 according to the literature (11,25). As colonoscopy can only detect lesions on the mucosal surface of the large intestine and terminal ileum, some characteristics of deep lesions and small intestine manifestations remain unveiled.…”
Section: B C Amentioning
confidence: 89%
See 1 more Smart Citation
“…Under colonoscopy, ≤5, round, focal, non-aphthous and non- cobblestone lesions were suggestive of intestinal BD, whereas longitudinal and multiple ulcers were suggestive of CD. The AUC of colonoscopy was 0.874-0.955 according to the literature (11,25). As colonoscopy can only detect lesions on the mucosal surface of the large intestine and terminal ileum, some characteristics of deep lesions and small intestine manifestations remain unveiled.…”
Section: B C Amentioning
confidence: 89%
“…Moderately high sensitivity and specificity were found for IUS in differentiating intestinal BD from CD. Several studies used other modalities, including demographic data, clinical manifestations, laboratory tests, cross-sectional imaging, and colonoscopic findings to differentiate the two diseases (9,11,12,(25)(26)(27). As for clinical manifestations, no gastrointestinal symptoms show a significant difference between BD and CD (7).…”
Section: B C Amentioning
confidence: 99%
“…Longitudinal ulcers in a discontinuous distribution and cobblestone appearance are endoscopic features of IBD. However, neurologic involvement is not observed in IBD [46][47][48][49][50].…”
Section: Differential Diagnosis Of Systemic Findingsmentioning
confidence: 99%
“…There were few reports on the incidence of intestinal BS in China, and the frequency of intestinal involvement among BS patients was about 17% reported from a small-sized case series (5). Our previous study found that some BS patients have typical ulcers under colonoscopy although they have no clinical symptoms of the gastrointestinal tract (6). Therefore, the frequency of intestinal BS in China may be higher than 17%.…”
Section: Introductionmentioning
confidence: 96%